Efficacy of allogeneic tendon material coracoclavicular ligament reconstruction combined with Kirschner wire and titanium alloy hook plate material fixation in the treatment of acromioclavicular joint dislocation - Du, Bing; Xu, Yibo; Li, Zhao; Ji, Shuai; Ren, Cheng; Li, Ming; Zhang, Kun; Ma, Teng (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To compare the effects of allogeneic tendon coracoclavicular ligament reconstruction combined with Kirschner wire fixation and clavicular hook plate fixation on early postoperative pain, postoperative shoulder joint function score and shoulder joint mobility in patients with acromioclavicular joint dislocation. Methods From January 2020 to January 2023, 43 patients with acromioclavicular joint dislocation admitted to Xi 'an Honghui Hospital were included. Among them, 24 patients were treated with the clavicular hook plate technique ( Hook Plate,HP) group, and 19 patients were treated with allogeneic tendon coracoclavicular ligament reconstruction combined with the Kirschner wire technique ( Allogeneic Tendon, AT) group. The Constant-Murley score of shoulder joint function six months after operation, postoperative shoulder joint activity, preoperative and postoperative pain, operation time, intraoperative blood loss and complications were compared between the two groups.Results All 43 patients were followed up for an average of 9.7 ( 9-12 ) months. The intraoperative blood loss in the allogeneic tendon group was less than in the hook plate group. The Constant-Murley shoulder function score was higher than that in the hook plate group 6 months after the operation. The abduction and lifting activity was greater than that in the hook plate group. The VAS scores at three days and 14 days after operation were lower than those in the hook plate group.There was 1 case ( 5.3 % ) of exudation around the Kirschner needle track in the allogeneic tendon reconstruction group, and 5 cases ( 20.8 % ) of complications in the hook plate group, including 1 case of internal fixation stimulation, 2 cases of acromion impingement syndrome, 1 case of acromioclavicular joint osteoarthritis, and 1 case of shoulder joint stiffness. The complication rate of the allogeneic tendon group was lower than that of the hook plate group.The clinical efficacy of allogeneic tendon coracoclavicular ligament reconstruction combined with Kirschner wire fixation in treating acromioclavicular joint dislocation ( Rockwood type III-V ) is better than hook plate internal fixation.The patients have less early postoperative pain and better recovery of shoulder joint function and shoulder joint mobility